The Effect of the Consentration of Sorbitol and Immersion Time on Quality of Dried Candied Papaya - Princen Rumahorbo; Terip Karo-Karo; Elisa Julianti (Jurnal Rekayasa Pangan dan Pertanian, 2015)
The purpose of this study was to determine the effect of the concentration of sorbitol and immersion time on the quality and sensory test of dried candied papaya. This study was using completely randomized design with two factors, i.e concentration of sorbitol (P) (40, 50, 60, 70, and 80%) and immersion time (R) (24, 48, and 72 hours). The analyzed parameters were water content (%), ash content (%), vitamin C content (mg/100 g sample), total acid content (mg/100 g sample), fruit hardness (kgf), total soluble solid (oBrix),  fiber content (%), and sensory test (color, flavor, taste, and texture). The results showed that concentration of sorbitol had highly significant effect on water content (%), ash content (%), vitamin C content (mg/100 g sample), total acid content (mg/100 g sample), fruit hardness (kgf), total soluble solid (oBrix), sensory test (taste); had  significant effect on flavor and taste and had no effect on fiber content (%), total sugar content (%), color and texture. The immersion time had highly significant effect on vitamin C content (mg/100 g sample), total acid content (mg/100 g sample), fruit hardness (kgf), and had no significant effect on water content (%), ash content (%), fiber content (%), total soluble solid (oBrix),  and sensory test (color, flavor, taste, and texture). The interaction of the factors had significant effect on fruit hardness (kgf). The best treatment which gave the best effect on papaya dried candy was 80% sorbitol and 48 hours of immersion time. Keyword : dried candied papaya, immersion time, sorbitol